Fixed points in MSn-algebras - Mendes, C. (2013)
An MSn-algebra, n ∈ N, is an Ockham algebra (L,∧,∨,f,0,1) satisfying x∧f^{2n}(x)=x. The class of all MSn-algebras is a variety denoted by MSn. For each subvariety V of MSn, we determine the admissible cardinalities of the set of fixed points of the (countable) algebras that generate V.